Computation Graphs for AAD and Machine Learning Part II: Application to Derivatives Risk Sensitivities. Issue 106 (23rd March 2020) - Savine, Antoine
Abstract : Third in a series of three articles with code, exploring the notion of computation graph, with words, mathematics and code, and application in Machine Learning and finance to compute a vast number of derivative sensitivities with spectacular speed and accuracy.